A triad amulet from Tel Azekah - Sweeney, Deborah; Herrmann, Christian; Ḳokh, ʿIdo; Gadot, Yuval; Oeming, Manfred; Lipshits, ʿOded (Israel exploration journal, 2018)
This article presents a highly unusual enstatite amulet discovered at Tel Azekah in 2015. It depicts two gods and a goddess, identified as the Egyptian deities Re-Horakhte, Seth and Hathor/Wadjet on the basis of their iconography and the inscription on the rear of the amulet. Though it lacks a secure archaeological context, we claim that it should be assigned to the Ramesside period on the basis of the deities depicted and mentioned in the inscription. The amulet is another indicator of the flourishing contacts between Azekah and Egypt during the twelfth century BCE.